Concepções de futuros professores de Ciências Físico-Químicas sobre a utilização de actividades laboratoriais - Ana Sofia Afonso; Laurinda Leite (Universidade do Minho, 2000)
Based on a constructiviste perspective of teaching and learning it is expected that prospective physical science teachers hold ideas about how physical science should be taught as well as that those ideas interfere with learning in university subjects that aim to prepare them for effective teaching. This is precisely the main aim of the didactics courses. The objective of this study is to diagnose the previous ideas on the use of the laboratory for physical science teaching brought to a didactics course by prospective teachers. In order to collect data, prospective teachers were asked to imagine themselves as 8th grade teachers and to describe a lesson to teach the concept of chemical reaction. The results indicate that prospective teachers would draw heavily on laboratory activities but in most cases they would not use them properly.